Sanatorium rehabilitation effects on vegetative test dynamics in myocardial infarction patients - A. N. Sumin; V. L. Beresneva; T. N. Enina; N. N. Verkhoshapova; E. A. Kabova; V. I. Valeeva; N. V. Shanaurina (Кардиоваскулярная терапия и профилактика, 2008)
Aim. To study dynamics of vegetative reflex tests (VRT) during sanatorium rehabilitation in patients with noncomplicated myocardial infarction (MI).Material and methods. In total, 106 men (mean age 48,6±1,0 years) were examined 44,3±3,2 days after MI, beforeand after sanatorium6based rehabilitation. Heart rate variability (HRV) was assessed during 24-hour electrocardiography (ECG), ECG at rest, active orthostatic test (AOT) and controlled breath rate test (CBRT). Physical stress tolerability (PST) and echocardiography parameters were also assessed.Results. After rehabilitation course, low frequency HRV component was increased in rest ECG (by 19 % for absolute values (p=0,06), by 5 % for normalized values (p=0,08)) and during AOT (by 27,3 % (р=0,015) and 6,2 % (р=0,011), respectively). CBRT results remained the same. Veloergometry PST increased by 10,1 %, end-systolic and end-diastolic left ventricular (LV) volumes decreased by 8,7 % and 6,6 %, respectively, asynergic area reduced by 6,0 %, and LV ejection fraction increased by 6,1 %. Rehabilitation adequacy was also confirmed by some decrease in mean HR and ventricular extrasystole rate during 246hour ECG monitoring.Conclusion. The results obtained could facilitate HRV data use in physical rehabilitation effectiveness assessment,optimizing and individual tailoring of rehabilitation programs.